Hubungan Efikasi, Sikap, Pengalaman Lepas, Dan Pengetahuan Dengan Amalan Pengajaran Pendidikan Alam Sekitar Merentasi Kurikulum Dalam Kalangan Guru Pelatih - Karthigasoo, Punitha Muniandy (2013)
A study on Environmental Education (EE) teaching practices among the Post Graduate Diploma (DPLI) teacher trainees’ in Teacher Training Institute (TTI) was conducted to investigate to what extend the across-curriculum subject is implemented by trainee teachers’ during their practicum. Earlier studies showed that teachers were still in their intermediate level of knowledge about EE. Even some teachers did not understand the concept of EE across the curriculum. The study of EE is necessary to evaluate the teacher trainees regarding their readiness for teaching across-curriculum during their teaching practicum. This study is essential to obtain information on the effectiveness of teaching and the problems encountered during the practicum by teacher trainees’. A Quan-qual mix method study was used for the study. The study consists of 670 respondents from the TTI in Malaysia. A set of questionaire was used to collect data to determine the effect of efficacy, attitude, experience and level of knowledge of EE among the teacher trainees’. The research instruments used were the "Environmental Education efficacy Belief Instrument" (EEBI), "Attitudes Toward Expressed Teaching Science" (EATTS), "Significant Life Experience" (SLE) and "Teaching Practise" (TP). Each one had a high reliability of 0.778 (EEBI), 0.830 (EATTS), 0.851 (SLE), and 0.840 (TP). The qualitative study were conducted by using lecturers’ observation forms and interviews with the participants. The observations and interviews data were analyzed to strenghten the quantitative findings.